Nokia's Shrinking Market Share in india (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Tho Powor of Focu - Nokia completely and sharply  focuaaod on mobllo phonos. Being ahead of the curve  was anothor component of Nokia's strategy In India, as  thoy had lnvosted beforo everybody else In the brand, in  tho pooplo, and most Importantly, In distribution. Nokia  lnvostod moro than 1 billion $In India which proves fts  focus on omorglng markets too. Tho Distribution Edge- Investments In people is  difficult to Judge, overy company claims to have the best  talon! In tho business. But whon It comes to distribution  Nokia takes tho lead. .Nokia started distributing Its  phonos through a partnership with HCL (formerly  Hindustan Computors Ltd)) which had already built an  oxtonslvo notwork for Its own products. Recently, Nokia  has dooldod to own distribution efforts and has opened  up storos In various cities.
Keywords: Nokia's strategy; distribution efforts; Distribution